ANALISIS YURIDIS ATAS PEMBERIAN KREDIT BARANG ELEKTRONIK OLEH BADAN USAHA TANPA IZIN - M. INDRA RACHMATSYAH IBRAHIM (PREMISE LAW JURNAL, 2017)
ABSTRACT   Consumer financing or the so-colled consumer credit is an operation of finance company which is incorporated and granted a permit for installment sale with leasing system for electronics and furniture to consumers. The research used normative judicial method which was analytical descriptive. The results showed that the levering of electronics by the lease seller which was a corporate without a permit in the leasing agreement was not an actual transfer of the ownership right from the lease seller to the lease buyer. Legal/valid because it had met all requirements stipulated in the Article. However, if it is reviewed form the Decree of the Minister of Finance of the Republic of Indonesia No. 448/KMK.017/2000 on Finance Company, a corporation without a permit which run the installment sale for electronics and furniture with the system of leasing agreement to the society had broken the law administratively because it did not have a permit issued by the authorized party to run all its activities.   Keywords : Lease Sale, Electronics and Furniture, Fiannce Company without Permit